Effects of palm fat blends inclusion on the quality of chicken frankfurters - Tan, S. S.; Abdullah, Aminah; Babji, Abdul Salam; Affandi, Mohd Suria (Universiti Putra Malaysia Press, 2002)
Three types of palm fats (PF) to be incorparated into meat batters were prepared from palm oil (PO) and palm stearin (POs) with the ratio ofpO:POs at 60:40, 70:30 and 80:20 (wt/wt). The slip melting point (SMP), iodine value (IV) and solid fat content (SFC) ofPF were measured. Eight formulations offrankfurters were then produced using PF60:40, PF70:30, PF80:20 and palm olein (POo) at 20% and 25% offat levels. Chopping temperature, emulsion stability (ES) and water holding capacity (WHC) ofmeat batters containing PF and POo were measured. At 25%fat level, meat batters mixed with PF60: 40 recarded the highest final chopping temperatures at the end of comminution, while POo recarded the lowest value. Fluid loss of meat batters prepared with PF60:40 and PF80:20 were significantly lower at 20% fat level compared to that of25%(P<0.05). Higher WHC was exhibited by meat batters containing various PF compared to the one with POo (P<0.05).